Newly developed type 1 diabetes after coronavirus disease 2019 vaccination: A case report. Issue 6 (11th February 2022) - Sasaki, Hironobu; Itoh, Arata; Watanabe, Yasuhiro; Nakajima, Yuya; Saisho, Yoshifumi; Irie, Junichiro; Meguro, Shu; Itoh, Hiroshi
Abstract: The vaccine for the coronavirus disease 2019 (COVID‐19) has been reported to potentially cause or worsen diabetes. A 73‐year‐old Japanese woman received two doses of Moderna COVID‐19 vaccine. Four weeks after the second vaccination, her glycemic control began to deteriorate, and 8 weeks after the second vaccination, the patient was diagnosed with new‐onset type 1 diabetes that was strongly positive for autoantibodies and showed a disease‐susceptible human leukocyte antigen haplotype, DRB1*04:05:01‐DQB1*04:01:01 . The glucagon stimulation test suggested an insulin‐dependent state, and induction of intensive insulin therapy brought about fair glycemic control. The time period from the COVID‐19 vaccination to the development of type 1 diabetes was relatively longer than to the onset or exacerbation of type 2 diabetes, as previously reported, suggesting the complicated immunological mechanisms for the destruction of β‐cells associated with the vaccination. In recipients with the disease‐susceptible haplotypes, one should be cautious about autoimmune responses for several months after the vaccination. Abstract : We experienced a case of newly diagnosed type 1 diabetes with strongly positivity for autoantibodies that developed after the coronavirus disease 2019 vaccination and showed a disease‐susceptible human leukocyte antigen haplotype. The time period from the coronavirus disease 2019 vaccination to the development of type 1 diabetes is relatively longer than to the onset or exacerbation of type 2 diabetes, as previously reported, suggesting the complicated immunological mechanisms for the destruction of β‐cells associated with the vaccination. In recipients with the disease‐susceptible haplotypes, one should be cautious about autoimmune responses for several months after the vaccination.